2009
DOI: 10.1016/j.fertnstert.2008.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Morbid obesity is associated with lower clinical pregnancy rates after in vitro fertilization in women with polycystic ovary syndrome

Abstract: Objective To determine if morbid obesity is associated with decreased pregnancy and live birth rates after IVF in women with PCOS Design Retrospective cohort study Setting University-based fertility center Patients 72 women with PCOS who completed their first IVF cycle between 2001 and 2007 Interventions IVF outcomes were compared between women with a BMI of less than 40 kg/m2 versus those women with a BMI of 40 kg/m2 or greater Main outcome measures Clinical pregnancy rate, live birth rate Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 27 publications
4
79
2
Order By: Relevance
“…Numerous studies have demonstrated decreased efficacy of fertility treatments in obese women 33,43 . As a result, some centers offering fertility treatments have put BMI limits on who they will treat and what types of treatment they will offer.…”
Section: Fertility Treatment For Obese Womenmentioning
confidence: 99%
“…Numerous studies have demonstrated decreased efficacy of fertility treatments in obese women 33,43 . As a result, some centers offering fertility treatments have put BMI limits on who they will treat and what types of treatment they will offer.…”
Section: Fertility Treatment For Obese Womenmentioning
confidence: 99%
“…Obese women with PCOS who also have hyperinsulinemia and impaired glucose tolerance are reported to have decreased fertilization and implantation rates compared to women with PCOS alone [9]. Morbidly obese women (BMI ≥40 kg/m) with PCOS have significantly lower pregnancy rates than women with PCOS alone [10]. The impact of obesity on reproductive health is particularly important because it can have long lasting consequences on future generations.…”
mentioning
confidence: 99%
“…With respect to obese women seeking pregnancy, the use of fertility treatments including assisted reproductive technology are costly and frequently associated with poorer success in obese women compared to normal-weight women [105,117,118]. During the assisted reproductive technology process, obese women have a poorer response to gonadotropins thus requiring much higher doses of these expensive medications, produce fewer and poorer quality oocytes, generate poorer quality embryos, achieve lower pregnancy rates, and have higher miscarriage rates [119][120][121][122]. This review presents a background framework for a new hypothesis suggesting the involvement of AGEs and their receptors in COH in obese women.…”
Section: Resultsmentioning
confidence: 99%